(untitled) (Numerus academy review, 2026)
The Constitutional Court is one of the most important judicial bodies in any legal system,and on this basis, the Algerian constitutional amendment of 2020, singled it out with a set of clearly and precisely defined powers, as the latter exercises constitutional control when it comes to ordinary laws before their issuance and treaties before ratification, and it is exercised as oversight Subsequent if it comes to regulations, within a month from the date of their publication, to examine the extent to which they do not conflict with the constitution, while the control of conformity is focused on organic laws, the internal regulations of the two chambers of Parliament, and legislative orders.